2008
DOI: 10.1117/12.793605
|View full text |Cite
|
Sign up to set email alerts
|

Refractive statistical concave 1D diffusers for laser beam shaping

Abstract: Certain high power laser applications require thin homogeneous laser lines. A possible concept to generate the necessary flat-top profile uses multi-aperture elements followed by a lens to recombine separated beamlets. Advantages of this concept are the independence from entrance intensity profile and achromaticity. However, the periodic structure and the overlapping of beamlets produce interference effects especially when highly coherent light is used. Random optical elements that diffuse only in one directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In addition our fabrication is very economical for scale up manufacturing, due to fast laser writing speeds, flexible and tailored pattering of glass substrates. 2 , 4 , 32 …”
Section: Resultsmentioning
confidence: 99%
“…In addition our fabrication is very economical for scale up manufacturing, due to fast laser writing speeds, flexible and tailored pattering of glass substrates. 2 , 4 , 32 …”
Section: Resultsmentioning
confidence: 99%
“…Through this and together with the optical power of the Fourier lens, the apertures are imaged to the plane FP. With the determination that a 12 …”
Section: Geometrical Description Of Microlens Beam Homogenizersmentioning
confidence: 99%
“…4.4. These diffusers are generated by isotropic etching of a mask of slits of fixed width that are statistically positioned across a fused silica substrate [12]. Long etch times can be used to generate elements with large radius of curvature and consequently small angular diffusion.…”
Section: Linear Static Diffusersmentioning
confidence: 99%
“…They suggested that a shaped beam profile can improve many laser processing applications. Previous studies have shown ingenuity in both the intensity profiles created [155][156][157][158] and in the methods used for creating them [159][160][161][162].…”
Section: Beam Shaping Technologies and Their Applicationsmentioning
confidence: 99%